(untitled) (Research, Society and Development, 2023)
Feeding the world’s population, based on the sustainability model is the greatest challenge of the 21st century, mainly in Brazil, which. Is one of the world’s main agricultural pillars. Nowadays, it stands out as important producer and exporter of agricultural products; however, it remains highly dependent on imported fertilizers and non-renewable raw materials. Moreover, it suffers from high economic costs. Therefore, remineralizers can be used as alternative to reduce both the use of, and production costs with, soluble mineral fertilizers. The objective of this research is to verify the agronomic efficiency of potential granite remineralizer K6, by Embu Engineering and Business, in soybean and silage corn crops planted in different of textural soil class. Experimental treatments encompassed increasing doses of potential remineralizer K6, namely: 30 kg. ha-1 K2O of K6, 60 kg. ha-1 K2O of K6, 120 kg. ha-1 K2O of K6, 240 kg. ha-1 K2O of K6, the reference treatment namely: 60 kg. ha-1 K2O of FMX remineralizer and, 60 kg. ha-1 K2O added with potassium chloride (KCl); and the witness treatment – all with four repetitions. Yield data have shown K release in the soil, which was absorbed by the test plants. This outcome has evidenced yield increase due to granite K6 application; consequently, K6 behavior was similar to that of FMX in the soil and, in some cases, similar to that of KCl. Potential granite remineralizer K6 helped optimizing the management of the herein tested cultures.